Sulfur assimilation and regulation of abiotic stress via OMICS - Bilal Ahmad Mir; Ritu Kumari; Gurmeen Rakhra; Parul Parihar; Rachana Singh; Aman Deep Raju; Prabhat Kumar Srivastava; Sheo Mohan Prasad; Richa Singh; Shefali Gulliya (Plant Stress)
Abiotic stress, which includes salinity, drought, heat, and cold, as well as their many combinations, severely reduces crop productivity across the globe each year. Considering the intensified worldwide climatic changes, the effects of these conditions on plant productivity become increasingly more concerning. Sulfur is essential for several metabolic processes, including the organization and control of electron transport. Reductive assimilation and integration into cysteine and methionine, sulfate absorption, and reductive assimilation and integration are the key methods that oxidized and reduced forms of organically bound sulfur get to their different roles. Protective compounds with sulfur, such as glutathione, phytochelatins, S-rich proteins, and several secondary metabolites, are essential for plants to survive abiotic stress, such as dihydroasparagusic acid, hydrogen sulfide, etc. This thorough review covered the regulation of sulfur at the protein and gene transcription levels in response to abiotic stress.